Street vendors' livelihood vulnerability to typhoons in Naga City, Philippines - Hidalgo, Hanilyn A.; Cuesta, Michael A.; Razafindrabe, Bam H.N. (2022)
Street vendors belong to the informal business sector operating outside the legal frameworks. With little or no access to social protection, they are perceived to be vulnerable to the adverse effects of a crisis or shocks like typhoons. This study assessed the livelihood vulnerability of street food vendors in an urban city in the Philippines by modifying Hahn's livelihood vulnerability model and the IPCC formula to construct a composite index for exposure, sensitivity, and adaptive capacity. Using the data obtained from the randomized survey of 100 street food vendors, principal component analysis revealed 10 latent variables related to livelihood vulnerability. These variables are business networks, business experience, human capital, financial capital, livelihood utilities, physical well-being, business risk management, physical damages, business losses, and shelter type. The index scores for each variable show that shelter type, business losses, business risk management, and financial capital are the leading factors of livelihood vulnerability among street food vendors; business network is the least. The overall vulnerability of the sector was found to be at a moderate level. One of the sector's major strengths is having social ties manifested through daily interactions and direct connections with their clients. The study offers a framework for measuring the vulnerability of the informal business sector to climate hazards that is context-specific and multifaceted, encompassing adaptive capacity, sensitivity, and exposure – distinctly integrating an entrepreneurial context indicative of business continuity as a livelihood vulnerability-reducing strategy.
Keywords: Street vendors; Urban economics